Electrolyte-enriched milk is as effective as oral electrolyte solution in correcting imbalances in diarrheal calves - Fernanda Tamara Neme Mobaid Agudo Romão; Isabela Regina de Oliveira Honório; Kevelin Helena Merino; Priscilla Fajardo Valente Pereira; Júlio Augusto Naylor Lisbôa (Ciência Rural)
ABSTRACT: Oral rehydration in calves is traditionally performed by administering an oral electrolyte solution in which the electrolyte concentrate (EC) is diluted in water. Dilution of EC in milk has been used as an alternative method because it encourages voluntary water intake. Although practical, its effectiveness has not been proven consistently. This study compared the effectiveness of these two rehydration methods for correcting imbalances in diarrheal calves. Twenty-four newborn calves with induced osmotic diarrhea were divided into two treatment groups: MG with EC diluted in milk at meals and WG with EC diluted in water (5% body weight at 4 and 12 hours). All calves were fed with milk (4% body weight at 0, 8, and 16 hours) and had free access to water. Venous blood samples were collected at the times: -48 (before induction), -24, 0 (start of treatment), 8, 16, 24, and 48 hours.Packed cell volume (PCV), total plasma protein (TP), pH, pCO2, HCO3 -, BE, Na+, K+, Cl-, L-lactate, creatinine, strong ion difference (SID3), anion gap (AG), total concentration of non-volatile weak acids (Atot), and percentage change in plasma volume (%PV) were measured or calculated. Calves exhibited moderate dehydration, hyponatremia, and mild strong ion acidosis. Both rehydration methods were effective in correcting the imbalances. Plasma volume expansion was faster in the WG and voluntary water intake was higher in the MG. Results based on induced rather than natural diarrhea are the main limitation of the study. Owing to its practicality and effectiveness, dilution of EC in milk can be used to treat non-depressed diarrheal calves with mild to moderate imbalances.